ChemInform Abstract: Nickel‐Catalyzed Directed Sulfenylation of sp2 and sp3 C—H Bonds. Issue 35 (September 2015) - Ye, Xiaohan; Petersen, Jeffrey L.; Shi, Xiaodong
Abstract Direct Ni‐catalyzed sulfenylation of the α‐methyl substituent of quarternary carboxylic amides bearing an aminoquinoline directing group is achieved by the reaction with aryl thiolates in the presence of LiOtBu as the base.